Evaluation of cortical venous drainage in patients with Acute Ischemic Stroke - Li, Runyang; Li, Xi; Li, Jie; Dai, Xinjun; Guo, Junhong; Wang, Shaoshuai (Frontiers in Neuroscience, 2025)
The emergence of Mechanical thrombectomy (MT) has changed the treatment modalities for Acute Ischemic Stroke (AIS). But still 45 to 55% of patients cannot achieve functional independence after sufficient recanalization through endovascular treatment, defined as “futile reperfusion.” Poor collateral circulation and microcirculation are key factors affecting prognosis. In the past, the assessment of these mainly focused on intracranial arteries and their collateral, neglecting the important role of the venous system in acute brain injury. More and more studies have found that “poor venous drainage” is associated with poor prognosis. However, there is currently no unified standard for the assessment of “cortical venous drainage.” This paper reviews the pathophysiology of the relationship between “cortical venous drainage” and prognosis, as well as the assessment methods and indicators of “cortical venous drainage,” aiming to provide a strong basis for the preoperative assessment of AIS patients and the selection of treatment plans.